2017
DOI: 10.1016/j.accpm.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

What are the therapeutic alternatives to dextropropoxyphene in France? A prescribers’ survey

Abstract: About a year after dextropropoxyphene (DXP) withdrawal from the French market, we conducted a survey among members of the French Society of Anesthesia & Intensive Care Medicine (Sfar) and of the French Society of the Study and Treatment of Pain (SFETD) to identify the indications for which this WHO level II analgesic had been prescribed, the prescriber's feedback following withdrawal, and the substitutive analgesics prescribed. DXP had been prescribed by more than 75% of the 430 anaesthesiologists and 230 pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
(6 reference statements)
0
3
1
Order By: Relevance
“…Of interest, the results of this study differ from the results of a survey performed among Pain specialists asked to describe alternatives to DXP in France [23]. HCPs declared tramadol combined with PC to be the substitutive analgesic of choice, while only 24% of considered PC alone as a substitute.…”
Section: Discussioncontrasting
confidence: 67%
“…Of interest, the results of this study differ from the results of a survey performed among Pain specialists asked to describe alternatives to DXP in France [23]. HCPs declared tramadol combined with PC to be the substitutive analgesic of choice, while only 24% of considered PC alone as a substitute.…”
Section: Discussioncontrasting
confidence: 67%
“…Prior to the publication of these guidelines, an impact study conducted in a French regional hospital had suggested that there may have been a switch towards the use of paracetamol and tramadol as a consequence of the withdrawal of dextropropoxyphene combinations [28]. A further survey conducted among prescribers involved in pain management confirmed this switch [29]. In our study, the increased consumption of paracetamol, ibuprofen and other mild opioids, was likely to result from the implementation of these guidelines by prescribing physicians.…”
Section: Figurementioning
confidence: 48%
“…Thus, the nonrational prescription of opioids grows, increasing the risk of public health consequences . The ease of administration of transdermal and transmucosal formulations may also partly explain the rise in prescriptions of fentanyl .…”
Section: Discussionmentioning
confidence: 99%
“…Following its suppression, all step 2 analgesics use rose during the immediate following years, before the switch clearly favoured tramadol. However, the withdrawal of dextropropoxyphene/paracetamol association can also partly explain the rise of step 1 analgesics use and the decrease of step 2 consumption, as not all dextropropoxyphene prescriptions were replaced by a step 2 drug, as this was previously described by other studies 7 8…”
Section: Discussion/conclusionmentioning
confidence: 83%